Inclusion, Education and Translanguaging How to Promote Social Justice in (Teacher) Education? - Panagiotopoulou, Julie A.; Rosen, Lisa; Strzykala, Jenna (Inklusion und Bildung in Migrationsgesellschaften, 2020)
This open access book is designed as an international anthology on the broader subject of inclusion, education, social justice and translanguaging. Prefaced by Ofelia García, the volume unites conceptional and empirical contributions focusing on various actors within educational institutions, from early childhood to secondary education and teacher training, while offering insights into multiple European and North-American educational systems. Contents Translanguaging in Early Childhood Education Translanguaging in School Education Translanguaging from the Perspective of (Multilingual) Students, Teachers and Educators Target Groups Researchers and students in the fields of educational, social and political sciences Editors Professor Dr. Julie A. Panagiotopoulou, University of Cologne Professor Dr. Lisa Rosen, University of Cologne M.A. Jenna Strzykala, University of Cologne.